Practice and procedure of Parliament: with particular reference to Lok Sabha - Kaul, M. N.; Shakdher, S.L. (New Delhi, 1983)
Originally compiled by M.N. Kaul and S.L. Shakdher, the first edition of 'Practice and Procedure of Parliament' came out in 1968. Since then, this oft-quoted treatise has been revised five times, in 1972, 1978, 1991, 2001 and 2009, primarily to make the publication up to date with time in the background of amendments to the Constitution and existing laws, changes in the Rules of Procedure and Conduct of Business in the Lok Sabha, new precedents and conventions. With the fourth edition published in 1991, this volume has become the official publication of the Lok Sabha Secretariat. Various chapters in the volume elucidate the parliamentary practice and procedures with empirical evidences, rulings, observations and directions by the Chair. Besides the practice and procedures, the volume also throws light on aspects of functioning of the Parliament and its Committiees. Since its last publication in 2009, several measures pertaining to the working of the Lok Sabha through procedural innovations have been taken for making the parliamentary business smooth and orderly enabling it to reach out to the masses..
Keywords: Parliamentary practice - India